Pleuraherd auf Wanderschaft - Dadrich, Monika; Schneider, Till M.; Puderbach, Michael; Kauczor, Hans-Ulrich; Heußel, Claus Peter (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2012)
A 74-year-old man with bronchial carcinoma underwent radiofrequency ablation (RFA) due to poor pulmonary function. Therefore non-enhanced computed tomography (CT) of the chest was performed on two subsequent days. Besides the tumor, the CT scans showed a moving calcification in the pleural cavity. This extremely rare condition called thoracolithiasis is usually an incidental finding. Mostly it is asymptomatic and does not require any treatment. It should be considered as a differential diagnosis of a peripheral pulmonary nodule.